Microstructural and thermal analysis of warm-modified bitumen with palm oil boiler ash - Shuhaida Harun; Naeem Aziz Memon; Abdalrhman Milad; Muhammad Imran Khan; Norliza Mohd Akhir; Muhamad Nazri Borhan; Nur Izzi Md Yusoff (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper presents the results of an investigation to evaluate the effect of Palm Oil Boiler Ash (POBA) and a chemical warm mix additive, Rediset on the physicochemical and thermal properties of bituminous binders. Modified binder preparation was carried out by varying the composition of POBA (0, 3, 5, 7, and 9%) and Rediset with 2% by total weight of the binder, into a 60/70 penetration grade of bitumen through a wet mixing method. The physicochemical properties of the POBA/Rediset modified binders were examined using Fourier Transform InfraRed (FTIR), while the thermal analysis was conducted using Differential Scanning Calorimetry (DSC), and Thermogravimetry analysis (TGA) techniques. Based on FTIR analysis, POBA/Rediset modified binders have almost similar functional groups as for the control sample (0%) which indicate the compatibility of POBA in the bituminous binder. Meanwhile, the thermos-grams shows an insignificant effect of POBA on the thermal stability of the binder. Overall, the inclusion of POBA as bitumen modifier in warm mix asphalt (WMA) for pavement construction is a promising and potential alternative in lowering the asphalt production temperature without compromising the binder properties.